SUMBER DAYA MANUSIA KANTOR DESA LANDIWO KECAMATAN LANDAWE KABUPATEN KONAWE UTARA - Saputri, Nining; Hadara, Ali (Jurusan Pendidikan Sejarah, Universitas Halu Oleo, 2020)
ABSTRACT: The research objective is to describe the Human Resources of the Landiwo Village Office, Landawe District, North Konawe Regency. The approach used in this research is a qualitative approach. Retrieval of data in research using literature studies, field studies, interviews and documentation. The results showed that (1) the ineffectiveness of the implementation of the village apparatus' duties could be identified through ineffective archiving or document storage activities, and even tended to fail to be implemented properly. The point is that the correspondence files that should be compiled and stored in the office but it is not done. However, the documents / archives of the Letters are not kept neat (scattered), so it is very difficult to find them again if needed. In addition, from the observations of researchers during the study, it was seen that village officials or officials were less effective in carrying out daily tasks, and even tended to be ineffective in terms of time discipline. This can be seen from the very limited presence of the apparatus on every working day, in fact it often happens that an officer does not come to the office for one week. In fact, sometimes on certain days the office was not open because no apparatus was present. As a result, services to the community are often carried out at the official's house, especially at the house of the Village Head or Village Secretary. This situation, makes it even clearer, that the implementation of village apparatus duties in village government administrative affairs is still ineffective. (2) Development of village apparatus resources is the preparation of individual village officials to take on different or higher responsibilities within the organization. The development referred to is related to the improvement of the intellectual or emotional abilities needed by village officials to do their jobs better and focus more on the long-term general needs of the organization. Human resource development for the Landiwo Village Office, Landawe District, Konawe Utara Regency, starts from the organization's HR plans because this plan analyzes, predicts, and mentions current and future organizational needs for human resources. In addition, HR planning anticipates the movement of people in the organization caused by retirement, promotions, and displacement. In addition, HR planning helps define the capabilities the organization will need in the future and the developments needed so that people can be available to meet the needs of the organization.